Rainfall Variability and Landuse Conversion Impacts to Sensitivity of Citarum River Flow - Marganingrum, Dyah; Sabar, Arwin; Roosmini, Dwina; Pradono, P (Forum Geografi, 2013)
The objective of this study is to determine the sensitivity of Citarum river flow to climate change and land conversion. It will provide the flow information that required in the water resources sustainability. Saguling reservoir is one of the strategic reservoirs, which 75% water is coming from the inflow of Upper Citarum measured at Nanjung station. Climate variability was identified as rainfall variability. Sensitivity was calculated as the elasticity value of discharge using three-variate model of statistical approach. The landuse conversion was calculated used GIS at 1994 and 2004. The results showed that elasticity at the Nanjung station and Saguling station decreased from 1.59 and 1.02 to 0.68 and 0.62 respectively. The decreasing occurred in the before the dam was built period (1950-1980) to the after reservoirs operated period (1986-2008). This value indicates that: 1) Citarum river flow is more sensitive to rainfall variability that recorded at Nanjung station than Saguling station, 2) rainfall character is more difficult to predict. The landuse analysis shows that forest area decrease to ± 27% and built up area increased to ± 26%. Those implied a minimum rainfall reduction to± 8% and minimum flow to ± 46%. Those were caused by land conversion and describing that the vegetation have function to maintain the base flow for sustainable water resource infrastructure.